2019
DOI: 10.6018/analesps.35.3.342671
|View full text |Cite
|
Sign up to set email alerts
|

Work Ethic: analysis of differences between four generational cohorts

Abstract: Las organizaciones enfrentan el reto de gestionar una fuerza laboral multigeneracional con características propias que difieren en el valor que le otorgan al trabajo. La incorporación al mercado laboral de las generaciones más jóvenes hace imprescindible el estudio de sus diferentes actitudes hacia el trabajo en comparación con las generaciones antecesoras. El propósito de la investigación fue analizar a través del constructo de la ética protestante las diferencias existentes en las actitudes hacia el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…When AEV is considered as the main variable, this situation coincides with the results of Despite the finding that AEV do not differ between generations, as stated in the conceptual framework, the fact that the case is mostly handled under the name of scientific ethics in the literature and the intergenerational differences in AEVR, which is the sub-dimension, made it possible to examine the finding under the name of scientific ethics. The intergenerational variation of AEVR was found in the study of Smola and Sutton (2002) [84] and Meriac et al's (2010) study [60] in terms of intergenerational differences in business ethics, in Ortega et al's (2019) study [65], between baby boomers GenX, GenY and GenZ, and Stevanin et al's (2020) finding a difference in the sub-dimensions of work ethics between the baby boomers, GenX and GenY are examples of how the difference can be detected in its sub-dimensions [90]. The difference in this study is that the silent generation has less ethical values than the baby boomers GenX and GenY in terms of the relevant sub-dimension is consistent with [21] stating that the silent generation gives less importance to work ethics than other generations.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…When AEV is considered as the main variable, this situation coincides with the results of Despite the finding that AEV do not differ between generations, as stated in the conceptual framework, the fact that the case is mostly handled under the name of scientific ethics in the literature and the intergenerational differences in AEVR, which is the sub-dimension, made it possible to examine the finding under the name of scientific ethics. The intergenerational variation of AEVR was found in the study of Smola and Sutton (2002) [84] and Meriac et al's (2010) study [60] in terms of intergenerational differences in business ethics, in Ortega et al's (2019) study [65], between baby boomers GenX, GenY and GenZ, and Stevanin et al's (2020) finding a difference in the sub-dimensions of work ethics between the baby boomers, GenX and GenY are examples of how the difference can be detected in its sub-dimensions [90]. The difference in this study is that the silent generation has less ethical values than the baby boomers GenX and GenY in terms of the relevant sub-dimension is consistent with [21] stating that the silent generation gives less importance to work ethics than other generations.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…PWE. PWE measurement was carried out through a reduced version of the Ecuadorian adaptation of the Multidimensional Work Ethic Profile (MWEP; Meriac et al 2013) developed by Zúñiga et al (2019). The scale has 28 items distributed equally in the seven dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…An example of an item on the scale is "A hard day's work gives me a feeling of accomplishment." The reliability of the dimensions (Zúñiga et al 2019) is adequate, receiving the following: delay of gratification (α = 0.777; ω = 0.786), hard work (α = 0.813; ω = 0.820), self-reliance (α = 0.676; ω = 0.679), moralityethics (α = 0.578; ω = 0.585), leisure (α = 0.712; ω = 0.715), centrality of work (α = 0.621; ω = 0.647) and wasted time (α = 0.596; ω = 0.642).…”
Section: Methodsmentioning
confidence: 99%
“…Diverse studies expose differences among generational cohorts regarding the work ethic dimensions (Zúñiga et al, 2019). Millennials or Generation "Y" are different from Generation "X" and Baby Boomers regarding Leisure, Hard Work, and Delay of Gratification; on the contrary, evidence has found that there are no intergenerational differences between members of the same family regarding PWE (James et al, 2020).…”
Section: Jel Codesmentioning
confidence: 99%
“…In terms of the instrument in Spanish (Woehr et al, 2007), before its application, a semantic-idiomatic review was carried out, with only minor modifications made in Ecuador (Zúñiga et al, 2019), while in Chile it was verified that all the words used were known and used daily by the sample because there were no changes. For data collection, all participants signed the respective informed consent form.…”
Section: Instrumentmentioning
confidence: 99%